Health Education Improved HIV/AIDS Knowledge among Middle School Students - Wafa Al Mufida; Edi Purwanto; Indah Dwi Pratiwi (Jurnal Kesehatan, 2026)
Adolescents are a population group vulnerable to HIV/AIDS transmission due to limited knowledge and the potential involvement in risky behaviors. This study aimed to analyze changes in HIV/AIDS knowledge after health education among adolescents. A quantitative approach with a one-group pretest-posttest design was employed. A total of 73 students participated in the study. Data were collected through pretest and posttest assessments using the HIV Knowledge Questionnaire-18 (HIV-KQ-18). The data were analyzed using the Wilcoxon Signed-Rank Test. The mean knowledge score increased from 7.10 before the intervention to 15.14 after the intervention, and the difference was statistically significant (Z = -7.552, p < 0.001). Within the limitations of a one-group pretest-posttest design without a control group. The findings suggest that health education has the potential to improve HIV/AIDS knowledge among adolescents.